Bacterial community response to a preindustrial‐to‐future CO2 gradient is limited and soil specific in Texas Prairie grassland. (7th October 2018) - Raut, Swastika; Polley, Herbert W.; Fay, Philip A.; Kang, Sanghoon
Abstract: Rising atmospheric CO2 concentration directly stimulates plant productivity and affects nutrient dynamics in the soil. However, the influence of CO2 enrichment on soil bacterial communities remains elusive, likely due to their complex interactions with a wide range of plant and soil properties. Here, we investigated the bacterial community response to a decade long preindustrial‐to‐future CO2 gradient (250–500 ppm) among three contrasting soil types using 16S rRNA gene amplicon sequencing. In addition, we examined the effect of seasonal variation and plant species composition on bacterial communities. We found that Shannon index ( H ') and Faith's phylogenetic diversity (PD) did not change in response to the CO2 gradient ( R 2  = 0.01, p  > 0.05). CO2 gradient and season also had a negligible effect on overall community structure, although silty clay soil communities were better structured on a CO2 gradient ( p  < 0.001) among three soils. Similarly, CO2 gradient had no significant effect on the relative abundance of different phyla. However, we observed soil‐specific variation of CO2 effects in a few individual families. For example, the abundance of Pirellulaceae family decreased linearly with CO2 gradient, but only in sandy loam soils. Conversely, the abundance of Micromonosporaceae and Gaillaceae families increased with CO2 gradient in clay soils. Soil water content (SWC) and nutrient properties were the key environmental constraints shaping bacterial community structure, one manifestation of which was a decline in bacterial diversity with increasing SWC. Furthermore, the impact of plant species composition on community structure was secondary to the strong influence of soil properties. Taken together, our findings indicate that bacterial communities may be largely unresponsive to indirect effects of CO2 enrichment through plants. Instead, bacterial communities are strongly regulated by edaphic conditions, presumably because soil differences create distinct environmental niches for bacteria. Abstract : We investigated the bacterial community response to a decade‐long preindustrial‐to‐future CO2 gradient (250–500 ppm) among three contrasting soil types using 16S rRNA gene amplicon sequencing. We found that bacterial communities may be largely unresponsive to indirect effects of CO2 enrichment through plants. Instead, bacterial communities are strongly regulated by edaphic conditions, presumably because soil differences create distinct environmental niches for bacteria.